Monitoring and evaluating agricultural research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Monitoring and evaluating agricultural research: a sourcebook edited by D Horton, P Ballantyne, W Peterson B Uribe, D Gapasin and K Sheridan 1993 240pp ISBN 0 85198 860 1 Pbk price UKL 17.95